Alkol kullanım bozukluğunun detoksifikasyon tedavisi sırasında yoksunluk şiddeti ile inflamasyon parametreleri arasındaki ilişki - Zengin İspir, Gamze and Tulacı, Rıza Gökçer (Journal of Dependence, 2024)
Objective: Alcohol withdrawal is a potentially life-threatening condition that could be seen after discontinuation or a decrease in alcohol consumption. Inflammatory processes take part in alcohol withdrawal duration. This study aimed to investigate the relationship between withdrawal severity and inflammation parameters. Method: This retrospective study was performed via electronic health records in an alcohol and drug treatment center between August-2021 and August-2022. One hundred forty-one inpatients with alcohol use disorder and 134 controls were enrolled. Sociodemographic, clinical, and biochemical data of the participants were collected. Results: The patients and the control group were similar in age, gender, and educational status. The patients’ group had higher levels of neutrophils and lower levels of lymphocytes than the control group. Neutrophil-to-lymphocyte (NLR) and monocyte-to-lymphocyte ratio (MLR) levels were higher in the patients’ group. The alcohol withdrawal severity of patients was positively correlated with NLR levels, MLR levels, the amount of daily alcohol, and years of heavy alcohol consumption. Conclusion: NLR and MLR are inexpensive and easily accessible markers that could be used to estimate alcohol withdrawal severity.